Universal Spirit Oleg Vinogradov's Romeo and Juliet in Korea - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Oleg Vinogradov's new Romeo and Juliet. This new Korean production, Vinogradov's tenth staging of Romeo and Juliet, suggests an almost obsessive fascination with Prokofiev's score. PALABRAS CLAVE: Oleg Vinogradov, Romeo and Juliet, Leonid Lavrovsky.